MEASURES TO IMPROVE THE EFFICIENCY OF THE PRODUCTION OF AGRICULTURAL CULTURES ON THE EXAMPLE OF THE SECK KOLKHOZ-PLEMING PLANT «KAZMINSKIY» - I. Kostornyy; E. Lepyakhova (Вестник Северо-Кавказского федерального университета, 2022)
The purpose of the article is to review the efficiency of production of grain crops in the SEC collective farm-breeding plant «Kazminsky». An analytical table was compiled, revealing the main economic indicators affecting the efficiency of grain production. A qualitative analysis of indicators. Identified three key factors affecting the efficiency, namely, agrobiological, technical, technological, organizational and economic. Real and appropriate measures are proposed for leveling the influence of each of the factors, with specific examples of implementation. In conclusion, the calculated effectiveness of the implementation of each of the activities.